FORMATION, CHARACTERISATION, AND MODELLING OF AEROBIC GRANULAR SLUDGE SYSTEM FOR TEXTILE WASTEWATER TREATMENT - Choerudin
Aerobic granular sludge (AGS) will be a new in biological wastewater treatment in the future. The application of AGS for industrial wastewater treatment is currently still in the research stage and will lead to the treatment of wastewater containing complex pollutants such as textile wastewater. The obstacle that is still faced in the application of the AGS system for textile wastewater treatment is the low productivity of granule formation (82.4 mg granule L-1 reactor day-1). Efforts to increase the productivity of granule formation are still needed. This research is related to the formation of AGS by using synthetic textile wastewater with several variations of the system (based on the concept of bioprocess). The research was conducted through two experimental stages. The first experiment studied the effect of the operating mode, namely the sequencing batch reactor (SBR) with constant volume (SB3) and varying volume (SB4), as well as the effect of the nutrient ratio COD:N:P, which was 100: 6,3: 2,4 (1× P), 100 : 6.3 : 12 (5×P), and 100 : 6.3 : 24 (10×P). The second experiment studied the influence of environmental conditions, namely pH and duration of aeration. The influence study was conducted in order to get an idea of increasing AGS production that can be carried out both in macro and microscale. The experimental data are used to build an empirical model so that through this model the best system for producing granules can be determined. The results of this study indicate that the formation of AGS is strongly influenced by both the operating mode and the nutrient ratio. Some things in the formation of AGS are only influenced by the ratio of nutrients so that the right combination of the two can have a good impact on the formation of AGS. Meanwhile, the formation of AGS was more influenced by the nutrient ratio and less influenced by environmental conditions. The impact of increasing the ratio of nutrients to several things is also shown in this study. The macro impacts include an increase in biomass accumulation and an increase in the rate of attainment of granular sludge requirements. The microscale impacts include on morphology, namely an increase in the maximum average diameter and maturation rate at certain operating modes, an increase in circularity from low to medium, but not roundness; and on microstructure, namely increasing the potential for sedimentation, the potential for decreasing the abundance of microbes but at the same time enriching certain types of functional microbes. The proposed mechanism for the formation of AGS related to increased nutrition is also the result of this study. This research produces "assessment tools" for a system in producing AGS that considers several aspects of the assessment. These results are very useful for the formation of AGS on a larger scale or in other types of wastewater. However, these results are limited only to systems that follow a linear-exponential model in biomass accumulation and in the transformation of biomass from floccules to granules, as well as following the unification-Gompertz model in granule size maturation. The derived parameters that can provide an assessment of the AGS formation system are: (1) “Sludge accumulation index” which assesses the amount of AGS that can be produced; (2) “Sludge transformation index” which assesses the speed at which the flocculated sludge transforms into granular sludge; and (3) “Granule proportion index” which assesses the size of the granule that can be produced which is proportional to the rate of formation. Thus, the system that produces large, fast, and good AGS (uniform size and shape) can be identified. The best result of this study was the combination of the SB3 system with a nutrient ratio of 5×P. AGS produced from this system had the lowest biomass accumulation of 2.7 g/L with an accumulation rate of 0.16 g/L/day. This AGS reached SVI = 90 mL/g (as a condition for granule slurry) on day 11 of granulation. The COD and color removal performance of the AGS reached 81% and 95%, respectively. The AGS is of medium size (1.0 – 1.4 mm) with a maturation rate of 0.16 mm/day and uniform in shape, with low roundness of 0.55 ± 0.11 and medium roundness of 0.63 ± 0, 11. The AGS has an abundance of 589 OTU (operational taxon units) microbes with a uniqueness of 37% (the type of microbe has not been identified taxonomically). The AGS consists of a group of microbes that decompose organic substances and decompose textile dyes, which are dominated by bacteria of the type Thermomonas and Rhodanobacter with typical physiological characteristics of facultative anaerobes, forming biofilms, and being able to withstand extreme conditions. Future research opportunities are to study further the relationship between the variety and abundance of microbial communities and the content of sediment particles found in the AGS on the removal performance or on the stability of the AGS. Another opportunity is to develop a more universal model that includes aspects of the quantity and quality of the produced granules and that describes the stability in the long term.